Analysis of Primary Drainage System Capacity in Supporting Urban Flood Resilience for the NUFReP Project - Muziburrahman Muziburrahman; Muh. Apriansyah; Sulis Syaputri (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Urban flooding in Santi Village, Bima City, remains a problem despite the implementation of the National Urban Flood Resilience Project (NUFReP). This study aims to analyze the capacity of the primary drainage system to support urban flood resilience. The study employs a mixed-methods approach through hydrological and hydraulic analyses, as well as modeling using the Storm Water Management Model (SWMM). The hydrological analysis yielded a design flood discharge of 14.79 m³/s, while the hydraulic analysis indicated a primary drainage capacity of 45.46 m³/s with a flow velocity of 2.37 m/s. The SWMM simulation results showed that the water level remained below the channel’s peak elevation without any overflow or surcharging, indicating that the channel capacity remains adequate with a utilization rate of approximately 32.53%. The study concluded that the primary drainage capacity is still capable of accommodating the design flood discharge, while the potential for flooding is more significantly influenced by sedimentation, debris blockages, and suboptimal maintenance and connectivity of the drainage network.